2011
DOI: 10.5032/jae.2011.01030
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Job Satisfaction Among Selected Agriculture Faculty

Abstract: The construct of job satisfaction is rooted in Maslow's Hierarchy of Needs and Herzberg's Motivator-Hygiene Theory. The current study was conducted to ascertain the level of job satisfaction of faculty members specializing in agricultural communication, agricultural leadership, agricultural teacher education, and extension education and to determine which job factors are the greatest predictors of an individual's overall job satisfaction. Survey research methods were utilized to collect data from members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…For the purposes of this study, the researcher examined the potential impact of role conflict on job satisfaction. Given the possible outcomes of lower job satisfaction ratings, including intention to leave a job, Foor and Cano (2011) urged supervisors to be concerned with the job satisfaction of their employees. Researchers have studied job satisfaction as it relates to athletic trainers (McChesney & Peterson, 2005, Terranova & Henning, 2011 as well as intercollegiate athletic directors (Robinson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purposes of this study, the researcher examined the potential impact of role conflict on job satisfaction. Given the possible outcomes of lower job satisfaction ratings, including intention to leave a job, Foor and Cano (2011) urged supervisors to be concerned with the job satisfaction of their employees. Researchers have studied job satisfaction as it relates to athletic trainers (McChesney & Peterson, 2005, Terranova & Henning, 2011 as well as intercollegiate athletic directors (Robinson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In their study of job satisfaction among faculty members, Foor and Cano (2011) stressed that individuals such as department chairs, directors, deans and others involved in administration and supervision should be concerned with the job satisfaction of their employees. The supervisors of NCAA Division III athletic directors, noted Robinson et al (2003), have a vested interest in improving job satisfaction in the hope of reducing organizational attitudes and adaptive responses that would be viewed as detrimental to the organization.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Herzberg's motivator-hygiene or two-factor theory has been widely used to connect job satisfaction/dissatisfaction to human motivators (Foor & Cano, 2011;Robertson & Smith, 1985). Herzberg (1966) posited that humans have two sets of needs that are independent from each other.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These factors include salary, working conditions, and job related relationships (Lundburg et al, 2009;Pinder, 1998). Another criticism that has been posited is that the research conducted by Herzberg hasn't supported the idea of two independent factors: Motivators and hygiene (Foor & Cano, 2011;Lundberg et al, 2009;Steers & Porter, 1991). Despite these criticisms, Steers and Porter (1991) suggested that continually modifying this theory will lead to a more comprehensive and accurate list of factors to identify job satisfaction.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The most satisfying facet of a teacher's job is in helping students and working with peers (Harlow, 2008). Additionally, other intrinsic factors that influence strongly an individual job satisfaction are achievement, responsibility, growth, advancement, and recognition (Wiliams & Lankford, 2003;Foor & Cano, 2011;Matsuoka, 2015;Tran, 2015).…”
Section: Principal Leadership Behaviour and Teacher Job Satisfactionmentioning
confidence: 99%